EFFECTIVENESS OF PATROL OPERATIONS AT BITUNG CLASS II SEA AND COAST GUARD BASE IN PREVENTING ENVIRONMENTAL POLLUTION AT SEA BY COMMERCIAL VESSELS - Yoel Christian; Julien Biringan; Joice Ch. Kumaat (Journal of International Islamic Law, Human Right and Public Policy, 2026)
This study aims to analyze the effectiveness of patrol operations at the Bitung Class II Sea and Coast Guard Base (PLP) in preventing marine pollution by merchant vessels and to identify factors that hinder its effective implementation. The background of this study is the persistent gap between the ideal conditions of marine environmental surveillance and the reality in the field, where marine pollution caused by merchant vessel activities still occurs despite the existence of national and international regulations governing it. This study uses a qualitative approach with a public administration perspective. Data were collected through interviews, observations, and documentation, then analyzed descriptively qualitatively using an effectiveness approach that includes input, process, output, and outcome. The analysis focused on patrol planning and implementation, inter-agency coordination, and the availability of organizational resources. The results show that the effectiveness of patrol operations at the Bitung Class II PLP in preventing marine pollution by merchant vessels is not optimal. This is due to limited human resources, a lack of patrol fleets, budget constraints, and suboptimal coordination between related agencies. These conditions have resulted in uneven coverage of surveillance and the continued discovery of potential marine pollution violations in Bitung waters. In conclusion, the effectiveness of patrol operations is greatly influenced by institutional capacity and synergy between actors in the marine surveillance system. Therefore, it is necessary to strengthen resources, improve coordination, and optimize patrol strategies to support sustainable marine environmental protection.